Multiple objects detection using Separability Filter and Circular Hough Transform - Haniza, Yazid; Mohamed Rizon, Mohamed Juhari; Puteh, Saad; Ali Yeon, Md Shakaff; Sazali, Yaacob; Abdul Rahman, Mohd. Saad; Sugisaka, Masanori (Kolej Universiti Kejuruteraan Utara Malaysia, 2009)
Organized by Kolej Universiti kejuruteraan Utara Malaysia (KUKUM), 15th June 2006 at DKG 4 & DKG 5, Kubang Gajah, Arau, Perlis.